A silicone composition

CN117529514BActive Publication Date: 2026-10-30WACKER CHEMIE AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280043568.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-10
Publication Date
2026-10-30
Estimated Expiration
2042-01-10

AI Technical Summary

Benefits of technology

可根据需要在本发明的导热性有机硅组合物中进一步掺合其他成分。例如能够掺合氧化铁、氧化铈等耐热性提升剂;二氧化硅等粘度调节剂;着色剂;脱模剂等任意成分。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The present application relates to a light-weighted organic silicon composition with high thermal conductivity, which contains vinyl silicone oil, (C-1) aluminum hydroxide with an average particle size of greater than or equal to 0.1 μm and less than or equal to 4 μm, (C-2) aluminum hydroxide with an average particle size of greater than or equal to 4 μm and less than or equal to 20 μm, and (C-3) aluminum hydroxide with an average particle size of greater than or equal to 80 μm and less than or equal to 100 μm. The composition can be used in the technical field of thermal conductive materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermally conductive organosilicon compositions. Background Technology

[0002] CN104718254b Ex.1 discloses a polyurethane system containing various thermally conductive fillers (the filling rate of the thermally conductive fillers is 0.75). The composition contains aluminum hydroxide with average particle sizes of 125 μm, 40 μm, 2 μm, and 2.7 μm, wherein the amount of ultra-large 125 μm aluminum hydroxide particles is approximately 50 wt%, calculated based on a total thermally conductive filler weight of 100 wt%.

[0003] CN112778768a Ex.5 discloses a silicone gel system containing thermally conductive fillers, which contains vinyl silicone oil, hydrogen-containing silicone oil, catalyst, inhibitor, coupling agent octyltrimethoxysilane and aluminum hydroxide with different particle sizes, wherein the ratio of aluminum hydroxide with different average particle sizes is 1μm:10μm:60μm=1.5:2.5:6.

[0004] JP5304588B2 Ex.4 discloses a thermally conductive silicone composition containing vinyl silicone oil, hydrogen-containing silicone oil, alkoxy-modified silicone oil, and aluminum hydroxide of different particle sizes, wherein the ratio of aluminum hydroxide of different average particle sizes is 1μm:10μm:50μm=2:4:4. Summary of the Invention

[0005] The objective of this invention is to obtain a lightweight composition that still has low viscosity and high thermal conductivity at high filler contents.

[0006] This invention provides a composition comprising: (A) component, which is an organopolysiloxane, preferably (A-1) component, which is an organopolysiloxane having at least 2 alkenyl groups in one molecule; Optional component (B) is an organohydrogen-containing polysiloxane having at least two hydrogen atoms directly bonded to silicon atoms, wherein the amount of hydrogen atoms directly bonded to silicon atoms is 0.1 to 5.0 times the amount of alkenyl groups derived from component (A-1). (C) Component thermally conductive filler, (C) component contains 10-25wt% (C-1) aluminum hydroxide with an average particle size greater than or equal to 0.1μm and less than or equal to 4μm. For example, (C-1) has average particle sizes of 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, and 2.8 μm, and contents of 14 wt%, 16 wt%, 18 wt%, 20 wt%, 22 wt%, and 24 wt%. 18-37wt% (C-2) Aluminum hydroxide with an average particle size greater than or equal to 4μm and less than or equal to 20μm. For example, (C-2) has average particle sizes of 6, 8, 10, 12, 14, 16, and 18 μm, and contents of 20 wt%, 22 wt%, 24 wt%, 26 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, and 36 wt%. 48-65wt% (C-3) aluminum hydroxide with an average particle size greater than or equal to 80μm and less than or equal to 100μm. For example, (C-3) has an average particle size of 82, 84, 86, 88, 90, 92, 94, 96, and 98 μm, and a content of 50 wt%, 52 wt%, 54 wt%, 56 wt%, 58 wt%, 60 wt%, 62 wt%, and 64 wt%. Of (C-1), (C-2), and (C-3), based on a 100wt% content of component (C) in the composition, Optional component (D), which is a platinum group metal solidified catalyst, is 0.1-1,000 ppm relative to component (A-1) in terms of the mass of platinum group metals. The filling amount of the thermally conductive filler is greater than or equal to 0.88, preferably greater than or equal to 0.89, and more preferably greater than or equal to 0.90.

[0007] In this invention, the filler content = total thermally conductive filler content / total weight of the composition. Generally, a filler content greater than or equal to 0.88 is considered a high filler content.

[0008] The composition as described above, wherein the sum of all aluminum hydroxide is greater than 95 wt%, preferably greater than 99 wt%, more preferably greater than 99.9 wt%, calculated with all thermally conductive fillers accounting for 100 wt%.

[0009] The composition as described above, wherein the sum of all aluminum hydroxide is greater than 95 wt%, preferably greater than 99 wt%, more preferably greater than 99.9 wt%, calculated with all fillers accounting for 100 wt%.

[0010] The composition as described above, wherein the density of the composition is less than or equal to 2.4 g / cm³. 3 Preferably less than or equal to 2.2 g / cm³ 3 More preferably less than or equal to 2.1 g / cm³ 3 .

[0011] The composition as described above, wherein the thermal conductivity of the composition is greater than or equal to 3.1 W / mK, preferably greater than or equal to 3.2 W / mK, and more preferably greater than or equal to 3.3 W / mK.

[0012] The composition described above, wherein (C-1), (C-2) and (C-3) aluminum hydroxide are all in amorphous forms.

[0013] The composition as described above, wherein the amount of spherical filler is less than 10 wt%, preferably less than 1 wt%, calculated based on a composition weight of 100 wt%.

[0014] The composition as described above, wherein the amount of spherical alumina is less than 10 wt%, preferably less than 1 wt%, calculated based on a composition weight of 100 wt%.

[0015] In the composition described above, the content of Al(OH)3 in (C-1), (C-2) and (C-3) aluminum hydroxide is greater than or equal to 99.1%, preferably greater than or equal to 99.5%.

[0016] In the composition described above, the content of Na2O in (C-1), (C-2) and (C-3) aluminum hydroxide is less than or equal to 0.1%, preferably the sum of the contents of water-soluble Na2O and lattice-state Na2O is less than or equal to 0.1%.

[0017] In the composition described above, at least one of the aluminum hydroxides (C-1), (C-2) and (C-3) is surface-treated, preferably treated with component (E-1).

[0018] The composition as described above, wherein (C-1) is treated with component (E-1).

[0019] The composition as described above, wherein component (C) contains 10-20wt% (C-1) aluminum hydroxide with an average particle size greater than or equal to 0.5μm and less than or equal to 3μm. 20-35wt% (C-2) aluminum hydroxide with an average particle size greater than or equal to 7μm and less than or equal to 15μm. 50-60wt% (C-3) aluminum hydroxide with an average particle size greater than or equal to 85μm and less than or equal to 95μm. In (C-1), (C-2) and (C-3), the composition is calculated based on (C) component being 100 wt%.

[0020] In the composition described above, the weight ratio of surface-treated aluminum hydroxide to untreated aluminum hydroxide is less than 0.3, preferably less than 0.2, and more preferably less than 0.15.

[0021] The composition as described above, wherein the weight ratio of (C-1) / (C-3) is between 0.2 and 0.4, preferably between 0.22 and 0.38, for example 0.25, 0.27, 0.29, 0.31, 0.33, 0.35.

[0022] The composition as described above, wherein the weight ratio of (C-2) / (C-3) is between 0.2 and 0.8, preferably between 0.25 and 0.75, and more preferably 0.3, 0.4, 0.5, 0.6, or 0.7.

[0023] The composition as described above, wherein the ratio of the average particle size of (C-2) / (C-1) is between 8 and 12, preferably between 9 and 11, more preferably between 9.5 and 10.5, for example 9.6, 9.8, 10.0, 10.2, 10.4.

[0024] The composition as described above, wherein the ratio of the average particle size of (C-3) / (C-1) is between 70 and 120, preferably between 75 and 100, more preferably between 80 and 99, for example 82, 84, 86, 88, 90, 92, 94, 96, 98.

[0025] The composition as described above, wherein the ratio of the average particle size of (C-3) / (C-2) is between 7.0 and 12.0, preferably between 7.5 and 10, more preferably between 8.0 and 9.9, for example 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8.

[0026] The average particle size is defined as the cumulative average particle size (D50 median diameter) measured on a volume basis using a BECKMAN COULTER LS 13 320 particle size analyzer.

[0027] (C-1) Aluminum hydroxide was prepared using the solution method. 0.1 g of (C-1) sample was placed in 10 ml of anhydrous ethanol, ultrasonically dispersed (100 W) and stirred for 2 minutes to ensure complete dispersion of the aluminum hydroxide. 2-3 drops of the sample solution were then placed into the sample cell of the particle size analyzer.

[0028] (C-2) and (C-3) aluminum hydroxide (or other thermally conductive fillers with an average particle size greater than or equal to 7 μm) are prepared by dry powder method. An appropriate amount of the sample after being dried at room temperature is placed in the measuring cylinder of the particle size analyzer and inserted into the detection slot of the equipment.

[0029] In this invention, the particle size distribution of (C-1), (C-2) and (C-3) aluminum hydroxide is unimodal, or in other words, its particle size distribution satisfies a unimodal particle size distribution or an almost unimodal particle size distribution.

[0030] The almost single-peak particle size distribution mentioned in this invention refers to the presence of two or more peaks in the volume integral plot of the measured sample, but the volume integral area of ​​the main peak accounts for more than 80%, preferably more than 85%, more preferably more than 90%, and even more preferably more than 95%.

[0031] Spherical packing, which is generally spherical in shape, is a type of packing material obtained by chemical and / or physical (including heat treatment) processes from amorphous packing.

[0032] Spherical alumina is a product obtained by heat treatment of amorphous alumina, and its outer contour is generally spherical.

[0033] Preferably, the thermally conductive silicone composition further contains 1-100 parts by weight, more preferably 1-50 parts by weight, and more preferably 1-10 parts by weight of component (A) relative to 100 parts by weight, wherein component (E) is preferably any one or more of the following components (E-1): Component (E-1) is an alkoxysilane compound represented by the following general formula (1). R 1 a R 2 b Si(OR 3 ) 4-a-b (1) In the formula, R 1 Independently, it is an alkyl group having 1-24 carbon atoms, preferably an alkyl group having 6-24 carbon atoms, more preferably an alkyl group having 12-18 carbon atoms, R 2 Independently, it is a hydrocarbon group with 1-10 carbon atoms, either unsubstituted or substituted, preferably methyl or ethyl. 3 It is independently an alkyl group having 1-6 carbon atoms, preferably methyl or ethyl. a is an integer from 1 to 3, b is an integer from 0 to 2, and a+b is an integer from 1 to 3.

[0034] In this invention, the weight ratio of component (C) to component (E-1) is between 100 and 800, preferably between 200 and 500, and more preferably between 200 and 400.

[0035] Furthermore, the thermally conductive silicone composition preferably has a viscosity of less than 250,000 mPa·s at 25°C, more preferably less than 200,000 mPa·s, and even more preferably less than 170,000 mPa·s.

[0036] If it is such a thermally conductive silicone composition, it has excellent formability.

[0037] Furthermore, the present invention provides a thermally conductive organosilicon cured product, which is a cured product of a thermally conductive organosilicon composition.

[0038] If it is such a thermally conductive silicone curing material, then it has excellent thermal conductivity and lightweight properties.

[0039] As described above, with respect to the thermally conductive silicone composition of the present invention, by precisely adjusting the ratio of the silicone composition comprising a specific organopolysiloxane, a hydrogen-containing polysiloxane, and a thermally conductive filler, and by highly filling the substrate with the thermally conductive filler, it is possible to provide a silicone composition with a thermal conductivity of 3.1 W / m·K or higher and a density of 2.4 g / cm³. 3 The following is a thermally conductive silicone composition with high thermal conductivity and lightweight properties. This thermally conductive silicone curing material is particularly suitable as a thermally conductive material present at the interface between the thermal interface of heat-generating electronic components and heat dissipation components such as heat sinks or circuit boards, for cooling electronic components through thermal conduction.

[0040] As described above, the aim is to develop a thermally conductive silicone cured product (thermally conductive resin molded body) with high thermal conductivity and lightweight properties, and a thermally conductive silicone composition that can supply the cured product.

[0041] To achieve the above objectives, the inventors of this application conducted careful research and discovered that by precisely adjusting the ratio of a silicone composition containing a specific organopolysiloxane, a hydrogen-containing polysiloxane, and a thermally conductive filler, and by highly filling the substrate with the thermally conductive filler, it is possible to obtain a material with a thermal conductivity of 3.1 W / m·K or higher and a density of 2.4 g / cm³. 3 The present invention is accomplished by the following thermally conductive silicone curing material with high thermal conductivity and lightweight properties.

[0042] Specifically, the present invention is a thermally conductive organosilicon composition comprising: (A) Component, organopolysiloxane, preferably (A-1) component, alkenyl organopolysiloxane. The organopolysiloxane, as component (A), is the main component of the composition of the present invention. Generally, the main chain portion is basically composed of repeating diorganosiloxane units, which may contain branched structures or cyclic structures in part of the molecular structure; however, from the perspective of the mechanical strength and other physical properties of the cured product, linear diorganopolysiloxanes are preferred.

[0043] The alkenyl-containing organopolysiloxane, which is component (A-1), is an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in one molecule, and is preferably a major component of the composition of the present invention. Generally, the main chain portion is basically composed of repeating diorganosiloxane units, which may partially contain a branched structure or a cyclic structure in their molecular structure; however, from the perspective of the mechanical strength and other physical properties of the cured product, linear diorganopolysiloxanes are preferred.

[0044] As organic functional groups bonded to silicon atoms, examples include unsubstituted or substituted monovalent hydrocarbon groups, such as alkyl groups like methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups like cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups like phenyl, tolyl, xylyl, naphthyl, and biphenyl; aralkyl groups like benzyl, phenethyl, phenylpropyl, and methylbenzyl; and groups where the hydrogen atoms bonded to the carbon atoms of these groups are partially or completely replaced by halogen atoms such as fluorine, chlorine, and bromine, or cyano groups. The functional groups bonded to silicon atoms include, for example, chloromethyl, 2-bromoethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl, 3,3,4,4,5,5,6,6,6-nonafluorohexyl, etc.; representative functional groups are those with 1-10 carbon atoms, particularly representative ones are those with 1-6 carbon atoms, preferably unsubstituted or substituted alkyl groups with 1-3 carbon atoms such as methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl, cyanoethyl, etc.; and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl, fluorophenyl, etc. Furthermore, the organic functional groups bonded to silicon atoms are not limited to being all identical.

[0045] Furthermore, examples of alkenyl groups include vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, and cyclohexenyl, which typically have around 2-8 carbon atoms; among these, lower alkenyl groups such as vinyl and allyl are preferred, and vinyl is particularly preferred. Additionally, at least two alkenyl groups must be present in one molecule, and to ensure good flexibility of the obtained cured product, it is preferable that the alkenyl groups are present only at the silicon atoms at the ends of the molecular chain.

[0046] The viscosity of the organopolysiloxane of component (A) at 25°C is preferably in the range of 10-100,000 mPa·s, particularly preferably in the range of 50-50,000 mPa·s, particularly preferably in the range of 50-20,000 mPa·s, and particularly preferably in the range of 50-2,000 mPa·s. The organopolysiloxane of component (A) is preferably polydimethylsiloxane.

[0047] The viscosity of the alkenyl organopolysiloxane containing component (A-1) at 25°C is preferably in the range of 10-100,000 mPa·s, particularly preferably in the range of 50-10,000 mPa·s, especially preferably in the range of 50-1,000 mPa·s, and particularly preferably in the range of 50-200 mPa·s. If it is 10 mPa·s or higher, the obtained composition exhibits good storage stability; furthermore, if it is 100,000 mPa·s or lower, the obtained composition exhibits good extensibility. The alkenyl organopolysiloxane containing component (A-1) is preferably a vinyl-terminated polydimethylsiloxane.

[0048] The organopolysiloxane of component (A) can be used alone or in combination with two or more organopolysiloxanes of different viscosities.

[0049] The alkenyl organopolysiloxane of component (A-1) can be used alone or in combination with two or more alkenyl organopolysiloxanes with different viscosities.

[0050] Optional component (B): Organic hydrogen-containing polysiloxane The organohydrogen-containing polysiloxane in component (B) is an organohydrogen-containing polysiloxane having at least two, preferably two to one hundred, hydrogen atoms (Si-H groups) directly bonded to silicon atoms per molecule, and functions as a crosslinking agent for component (A-1). That is, the Si-H groups in component (B) undergo hydrosilylation with the alkenyl groups in component (A-1) via a hydrogenation reaction promoted by a platinum group metal curing catalyst of component (D) described later, thereby supplying a three-dimensional network structure with a crosslinked structure. Furthermore, when the number of Si-H groups in component (B) is less than two, curing is not possible.

[0051] As an organohydrogen-containing polysiloxane, the organohydrogen-containing polysiloxane represented by the following average structural formula (4) can be used, but is not limited thereto.

[0052] (4) In the formula, R' is an unsubstituted or substituted monovalent hydrocarbon group or hydrogen atom that does not contain aliphatic unsaturated bonds, but at least two R' are hydrogen atoms; e is an integer greater than or equal to 1.

[0053] In formula (4), R' is an unsubstituted or substituted monovalent hydrocarbon group other than hydrogen that does not contain aliphatic unsaturated bonds. Examples include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl; aralkyl groups such as benzyl, phenethyl, phenylpropyl, and methylbenzyl; and aralkyl groups in which the carbon atoms of these groups are partially or completely replaced by halogen atoms such as fluorine, chlorine, and bromine. Substituent groups such as cyano, for example, chloromethyl, 2-bromoethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl, 3,3,4,4,5,5,6,6,6-nonafluorohexyl, etc.; representative groups are those with 1-10 carbon atoms, particularly representative groups are those with 1-6 carbon atoms, preferably unsubstituted or substituted alkyl groups with 1-3 carbon atoms such as methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl, cyanoethyl, etc.; and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl, fluorophenyl, etc. Furthermore, R' is not limited to all being identical.

[0054] Regarding the amount of component (B), it is such that the Si-H groups derived from component (B) are 0.1-5.0 moles relative to 1 mole of alkenyl groups derived from component (A-1) (i.e., the number of moles of hydrogen atoms directly bonded to silicon atoms is 0.1-5.0 times the number of moles of alkenyl groups derived from component (A-1)). Preferably, the amount of Si-H groups derived from component (B) is 0.3-2.0 moles relative to 1 mole of alkenyl groups derived from component (A-1), and more preferably, the amount of Si-H groups derived from component (B) is 0.5-1.0 moles relative to 1 mole of alkenyl groups derived from component (A-1). If the amount of Si-H groups derived from component (B) is less than 0.1 moles relative to 1 mole of alkenyl groups derived from component (A-1), it may sometimes fail to cure, or the cured material may not have sufficient strength to maintain its shape as a molded body, thus making it impossible to work. Furthermore, if it exceeds 5.0 moles, the cured material will lack flexibility and may become brittle.

[0055] The organopolysiloxane of component (B) can be used alone or in combination with two or more organopolysiloxanes of different viscosities.

[0056] The composition as described above, wherein component (B) may comprise (B-1) and (B-2).

[0057] (B-1) is an organohydrogen-containing polysiloxane having at least 3, preferably 3-100, hydrogen atoms (Si-H groups) directly bonded to silicon atoms in one molecule, and having a hydrogen content between 0.5-4 mmol / g, preferably between 0.8-3 mmol / g, more preferably between 1.1-2.7 mmol / g, and even more preferably between 1.5-2.3 mmol / g.

[0058] The (B-2) component is an organohydrogen-containing polysiloxane having two hydrogen atoms (Si-H groups) directly bonded to silicon atoms in one molecule, and its hydrogen content is between 0.01-1.5 mmol / g, preferably between 0.1-1.2 mmol / g, more preferably between 0.3-1.0 mmol / g, and even more preferably between 0.4-0.8 mmol / g.

[0059] The composition as described above, wherein component (B) comprises (B-1) and (B-2), wherein the amount of component (B-1) is between 0.5-3 wt%, preferably between 1.5-2.5 wt%, calculated based on component (A-1) being 100 wt%.

[0060] The composition as described above, wherein component (B) comprises (B-1) and (B-2), wherein the amount of component (B-2) is between 10-50 wt%, preferably between 20-40 wt%, calculated with component (A-1) being 100 wt%.

[0061] (C) Composition: Thermally conductive filler Aluminum hydroxide can be used as a thermally conductive filler; it is inexpensive and has a density of 2.42 g / cm³. 3 Aluminum hydroxide (AOH) is much smaller than aluminum oxide (aluminum oxide), which can suppress the sedimentation of thermally conductive fillers in silicone compositions and contribute to the weight reduction of equipment. Furthermore, its Mohs hardness is 3, which is much softer than aluminum oxide, and it can suppress wear on reaction vessels and stirring blades, while also possessing flame-retardant and insulating properties. However, compared to aluminum oxide, aluminum hydroxide has a lower thermal conductivity. Therefore, although a high filler content of aluminum hydroxide is necessary to improve the thermal conductivity of silicone thermally conductive compositions and cured products, achieving such a high filler content is very difficult. Consequently, it has been difficult to achieve a thermal conductivity of 3.1 W / m·K or higher in thermally conductive silicone cured products where aluminum hydroxide accounts for more than 0.9% of the total mass of the thermally conductive filler. This invention overcomes the problems of the prior art by precisely adjusting the ratio of a silicone composition containing specific organopolysiloxanes, hydrogen-containing polysiloxanes, and thermally conductive fillers, and by high-filling the thermally conductive filler into the substrate, providing a thermally conductive silicone composition that can supply thermally conductive silicone cured products with high thermal conductivity and lightweight properties.

[0062] Preferably, component (C) contains 10-25 wt% (C-1) Aluminum hydroxide with an average particle size greater than or equal to 0.1 μm and less than or equal to 4 μm, for example, with average particle sizes of 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, and 2.8 μm. 18-37wt% (C-2) Aluminum hydroxide with an average particle size greater than or equal to 4μm and less than or equal to 20μm, for example, with average particle sizes of 6, 8, 10, 12, 14, 16, and 18μm. 48-65wt% (C-3) Aluminum hydroxide with an average particle size greater than or equal to 80μm and less than or equal to 100μm, for example, with average particle sizes of 82, 84, 86, 88, 90, 92, 94, 96, and 98μm. The amounts of (C-1), (C-2) and (C-3) mentioned above are calculated based on the fact that component (C) in the composition is 100 wt%.

[0063] By ingeniously combining particles of aluminum hydroxide with different particle sizes as the main component, namely by ingeniously combining the blending ratios of small, medium, and large-sized aluminum hydroxide particles (C-1), (C-2), and (C-3), the substrate can be highly filled by filling the gaps between large-sized particles with small and medium-sized particles.

[0064] On the other hand, if the average particle size of aluminum hydroxide in the above-mentioned components (C-1), (C-2) and (C-3) is outside the above-mentioned range, or if the composition ratio of (C-1), (C-2) and (C-3) is outside the above-mentioned range, it is impossible to prepare a thermally conductive organosilicon composition that can supply a thermally conductive organosilicon cured material with high thermal conductivity and light weight, having a thermal conductivity of 3.1 W / m·K or higher and a low viscosity.

[0065] In addition, the above average particle size is the cumulative average particle size (D50 median diameter) on a volume basis, measured using a BECKMAN COULTER LS 13 320 particle size analyzer.

[0066] The small-particle-size aluminum hydroxide (filler) component (C-1), when combined with the medium- and large-particle-size aluminum hydroxide components (C-2) and (C-3), can improve the thermal conductivity and flowability of the composition and prevent filler sedimentation. The average particle size is greater than or equal to 0.1 μm and less than or equal to 4 μm, preferably 1-2 μm. If the average particle size is outside the above range, the effects of improving the thermal conductivity and flowability of the composition and preventing filler sedimentation, achieved by combining it with components (C-2) and (C-3), cannot be obtained. One type of aluminum hydroxide or two or more types can be used as component (C-1).

[0067] The amount of component (C-1) is 10-25 wt%, preferably 19-21 wt%. If the mass ratio is outside the above range, the effects of improving the thermal conductivity and flowability of the composition and preventing filler sedimentation, which are achieved by combining it with components (C-2) and (C-3), cannot be obtained.

[0068] Large-particle-size aluminum hydroxide (filler) of component (C-3) can significantly improve thermal conductivity. The average particle size of the large-particle-size aluminum hydroxide is greater than or equal to 80 μm and less than or equal to 100 μm, preferably 85-95 μm. If the average particle size is outside the above range, the effect of improving thermal conductivity is reduced, and in addition, the viscosity of the composition increases and the processability deteriorates. One type of aluminum hydroxide or two or more types can be used as component (C-3).

[0069] The amount of component (C-3) is 50-65 wt%, preferably 58-63 wt%. If the mass ratio is outside the above range, the effect of improving thermal conductivity is reduced, and in addition, the viscosity of the composition increases and the processability deteriorates.

[0070] The amounts of (C-1), (C-2) and (C-3) mentioned above are calculated based on the fact that component (C) in the composition is 100 wt%.

[0071] Thermally conductive fillers generally do not include fumed silica or precipitated silica.

[0072] In the composition of the present invention, the content of fumed silica and / or precipitated silica is less than 1 wt%, preferably less than 0.1 wt%, calculated based on a total composition of 100 wt%.

[0073] Other thermally conductive fillers are not particularly limited, but for example, non-magnetic metals such as copper and aluminum; metal oxides such as aluminum oxide, magnesium oxide, iron oxide, beryllium oxide, titanium oxide, and zirconium oxide; metal nitrides such as aluminum nitride, silicon nitride, and boron nitride; metal hydroxides such as magnesium hydroxide; and substances commonly considered thermally conductive fillers such as synthetic diamond or silicon carbide can be used. Furthermore, the particle size can be 0.1-200 μm, and one type or two or more types can be used.

[0074] The amount of component (C) should be 800-4,000 parts by weight relative to 100 parts by weight of component (A), preferably 900-2,000 parts by weight, and more preferably 900-1,500 parts by weight. When the amount of component (C) is less than 800 parts by weight, the resulting composition has poor thermal conductivity; when it exceeds 2,000 parts by weight, the kneading operability is poor, and the cured product becomes significantly brittle. To obtain a high thermal conductivity and a lightweight product, the filler content of the composition is generally greater than or equal to 0.88.

[0075] Optional (D) component: Platinum group metal curing catalyst (D) Platinum group metal curing catalysts are not particularly limited as long as they are catalysts used to promote the addition reaction of alkenyl groups derived from (A-1) and Si-H groups derived from (B). Known catalysts can be listed as catalysts for hydrosilylation reactions. Specific examples include platinum group metals such as platinum (including platinum black), rhodium, and palladium; H₂PtCl₄·nH₂O, H₂PtCl₆·nH₂O, NaHPtCl₆·nH₂O, KHPtCl₆·nH₂O, Na₂PtCl₆·nH₂O, K₂PtCl₄·nH₂O, PtCl₄·nH₂O, PtCl₂, and Na₂HPtCl₄·nH₂O. (Where, in the above formula, n is an integer from 0 to 6, preferably 0 or 6) such as platinum chloride, chloroplatinic acid, and chloroplatinate; alcohol-modified chloroplatinic acid (refer to US Patent No. 3,220,972), complexes of chloroplatinic acid with olefins (refer to US Patent Nos. 3,159,601, 3,159,662, and 3,775,452); substances containing platinum group metals such as platinum black and palladium supported on supports such as alumina, silica, and carbon; rhodium-olefin complexes; tris(triphenylphosphine) rhodium chloride (Wilkinson catalyst); complexes of platinum chloride, chloroplatinic acid, or chloroplatinate with vinylsiloxanes, especially vinylcyclic siloxanes, etc.

[0076] The amount of component (D) used relative to component (A-1), converted to the mass of platinum group metals, is 0.1-1,000 ppm. If less than 0.1 ppm, sufficient catalytic activity cannot be obtained; even if it exceeds 1,000 ppm, the effect of promoting the addition reaction will not be improved, but the cost will be increased, and the catalyst will remain in the solidified material, so the insulation may be reduced.

[0077] (E) Components: Surface treatment agent In preparing the composition, a surface treatment agent of component (E) can be incorporated into the composition of the present invention. The purpose of this is to hydrophobize the thermally conductive filler, which is component (C), improve its wettability with the organopolysiloxane, which is component (A), and uniformly disperse the thermally conductive filler, which is component (C), in the matrix composed of component (A). As component (E), component (E-1) shown below is particularly preferred.

[0078] (E-1) Composition: Alkoxysilane compounds represented by the following general formula (1).

[0079] R 1 a R 2 b Si(OR 3 )4-a-b (1) In the formula, R 1 Independently, it is an alkyl group having 1-24 carbon atoms, preferably an alkyl group having 6-24 carbon atoms, more preferably an alkyl group having 12-18 carbon atoms, R 2 Independently, it is a hydrocarbon group with 1-10 carbon atoms, either unsubstituted or substituted, preferably methyl or ethyl. 3 Independently, it is an alkyl group having 1-6 carbon atoms, where a is an integer from 1 to 3, b is an integer from 0 to 2, and a+b is an integer from 1 to 3.

[0080] In the above general formula (1), R is used as 1 The alkyl group represented can be, for example, hexyl, octyl, nonyl, decyl, dodecyl, tetradecyl, etc. If the R... 1 If the number of carbon atoms of the alkyl group is in the range of 6-15, then the wettability of component (A) is sufficiently improved, the workability is good, and the low-temperature properties of the composition are good.

[0081] As R 2 The unsubstituted or substituted hydrocarbon groups referred to include, for example, alkyl groups such as methyl, ethyl, vinyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl; aralkyl groups such as benzyl, phenethyl, phenylpropyl, and methylbenzyl; and groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups are replaced by halogen atoms such as fluorine, chlorine, and bromine, or cyano groups. Examples include chloromethyl, 2-bromoethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl, 3,3,4,4,5,5,6,6,6-nonafluorohexyl, etc.; representative groups are those with 1-10 carbon atoms, particularly representative groups are those with 1-6 carbon atoms, preferably unsubstituted or substituted alkyl groups with 1-3 carbon atoms such as methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl, cyanoethyl, etc.; and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl, fluorophenyl, etc.

[0082] As R 3 Examples of possible compounds include methyl, ethyl, propyl, butyl, and hexyl. Furthermore, there are no particular limitations as long as a is an integer from 1 to 3, b is an integer from 0 to 2, and a+b is an integer from 1 to 3, but it is preferred that a is 1 and b is 0.

[0083] The (E-1) component is preferably an alkoxysilane containing a C6-18 long-chain alkyl group; more preferably a trialkoxysilane containing a C6-18 long-chain alkyl group; even more preferably hexadecyltrimethoxysilane, hexadecyltriethoxysilane, tetradecyltrimethoxysilane, tetradecyltriethoxysilane, dodecyltrimethoxysilane, or dodecyltriethoxysilane.

[0084] The surface treatment agent used as component (E) can be any one of components (E-1), or a combination of several. In this case, as component (E), it is preferably 1-100 parts by mass, more preferably 1-50 parts by mass, and more preferably 1-10 parts by mass relative to 100 parts by mass of component (A).

[0085] (F) Ingredients: Property enhancers As component (F), an organopolysiloxane with a viscosity of 10-100,000 mPa·s at 25°C, represented by the following general formula (3), can be added. Component (F) can be appropriately used for the purpose of imparting properties such as viscosity modifiers or plasticizers to the thermally conductive organosilicon composition, but is not limited thereto. A single organopolysiloxane may be used, or two or more may be used simultaneously.

[0086] (3) In the formula, R 5 Independently, it is a monovalent hydrocarbon group with 1-10 carbon atoms that does not contain aliphatic unsaturated bonds, and d is an integer from 5 to 2,000.

[0087] The above R 5 Independently, it is a monovalent hydrocarbon group with 1-10 carbon atoms, either unsubstituted or substituted. As R 5 Examples include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl; aralkyl groups such as benzyl, phenethyl, phenylpropyl, and methylbenzyl; and groups formed by replacing some or all of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms such as fluorine, chlorine, and bromine, or cyano groups, such as chloromethyl, 2-bromoethyl, 3-methyl... -Chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl, 3,3,4,4,5,5,6,6,6-nonafluorohexyl, etc.; representative groups are groups with 1-10 carbon atoms, particularly representative groups are groups with 1-6 carbon atoms, preferably unsubstituted or substituted alkyl groups with 1-3 carbon atoms such as methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl, cyanoethyl, etc.; and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl, fluorophenyl, etc.; particularly preferred are methyl and phenyl.

[0088] From the perspective of the required viscosity, the above-mentioned d is preferably an integer from 5 to 2,000, and particularly preferably an integer from 10 to 1,000.

[0089] Furthermore, the viscosity at 25°C is preferably 10-100,000 mPa·s, particularly preferably 100-10,000 mPa·s. If the viscosity is 10 mPa·s or higher, the cured product of the obtained composition is less prone to oil seepage. If the viscosity is 100,000 mPa·s or lower, the obtained thermally conductive silicone composition has suitable flexibility.

[0090] When component (F) is added to the thermally conductive silicone composition of the present invention, the amount added is not particularly limited, and can be 10-100 parts by weight relative to 100 parts by weight of component (A). If the amount added is within the range described above, it is easy to maintain the good flowability and workability of the thermally conductive silicone composition before curing, and it is easy to fill the composition with the thermally conductive filler of component (C).

[0091] In the thermally conductive silicone composition of the present invention, the amount of component (F) is preferably less than 0.1 parts by weight, more preferably less than 0.01 parts by weight, relative to 100 parts by weight of component (A). This avoids oil seepage and substrate contamination in the thermally conductive silicone composition.

[0092] Optional (G) component: Reaction inhibitor Addition reaction inhibitors can be used as component (G). All known addition reaction inhibitors commonly used in addition-curing silicone compositions can be used. Examples include acetylene compounds such as 1-ethynyl-1-hexanol and 3-butyn-1-ol; various nitrogen compounds; organophosphorus compounds; oxime compounds; organochlorine compounds, etc. The amount used as component (G) is preferably 0.01-1 parts by weight, more preferably 0.1-0.8 parts by weight, relative to 100 parts by weight of component (A-1). With such an amount, the curing reaction can proceed sufficiently without compromising molding efficiency.

[0093] Other ingredients Other components can be further incorporated into the thermally conductive organosilicon composition of the present invention as needed. For example, heat resistance enhancers such as iron oxide and cerium oxide; viscosity modifiers such as silica; colorants; release agents, and any other components can be incorporated. Detailed Implementation

[0094] Thermally conductive organosilicon cured products and their preparation methods The thermally conductive silicone cured product (thermally conductive resin molded body) of the present invention is a cured product of the above-mentioned thermally conductive silicone composition. The curing conditions for curing (molding) the thermally conductive silicone composition can be the same as those for known addition-curing silicone rubber compositions; for example, it can be fully cured at room temperature, but heating may be performed as needed. Addition curing at 100-120°C for 8-12 minutes is preferred. The cured product (molded body) of the present invention exhibits excellent thermal conductivity.

[0095] Thermal conductivity of the molded body The thermal conductivity of the molded body in this invention was measured using the transient planar heat source method (Hot Disk). At 25°C, the measured value of the composition of this invention is preferably 3.1 W / m·K or higher. If the thermal conductivity is 3.1 W / m·K or higher, it is suitable for heating elements with high heat generation. Furthermore, this thermal conductivity can be adjusted by changing the type or particle size combination of the thermally conductive filler.

[0096] Hardness of molded body The hardness of the molded article in this invention was measured using a Zwick hardness tester. Furthermore, the hardness can be adjusted by changing the ratio of component (A-1) to component (B) and thus adjusting the crosslinking density.

[0097] Example The kinematic and static viscosities of the compositions of the present invention were obtained using an Anton Paar MCR302 instrument according to DIN53019.

[0098] The (A)-(G) components used in the following examples and comparative examples are as follows.

[0099] (A) Ingredients: (A-1) The component is the organopolysiloxane represented by the following formula (5).

[0100] (5) X represents vinyl, and n represents the number of molecules that can be supplied with a viscosity of 120 mPa·s.

[0101] (B) Ingredients: (B-1) The hydrogen-containing polysiloxane with side chain represented by the following formula (6) has a hydrogen content of 1.7 mmol / g.

[0102] (6) (B-2) The end-group hydrogen-containing polysiloxane represented by the following formula (5) has X as hydrogen and a hydrogen content of 0.53 mmol / g.

[0103] (5) (C) Ingredients: (C-1-1) Aluminum hydroxide with an average particle size of 1.5 μm (C-1-2) Aluminum hydroxide with an average particle size of 1.5 μm, surface treated with composition (E-1). (C-2) Aluminum hydroxide with an average particle size of 10 μm (C-3) Aluminum hydroxide with an average particle size of 90 μm (C-4-1) Aluminum hydroxide with an average particle size of 50 μm (C-4-2) Aluminum hydroxide with an average particle size of 110 μm (D) Ingredients: 5wt% chloroplatinic acid 2-ethylhexanol solution (E) Components: hexadecyltrimethoxysilane (G) Ingredients: Ethynylmethylene methanol as an inhibitor of addition reaction.

[0104] The above-mentioned substances were provided by Wacker Chemie.

[0105] Add ingredients (A-1), (C), and (E) in the amounts specified in the examples and comparative examples shown in Tables 1 and 2 below, and knead for 60 minutes using a planetary mixer.

[0106] Add component (D) to the mixture in the amounts specified in Table 2 below and knead for 30 minutes.

[0107] Further, component (B) was added to the mixture in the amounts specified in Table 2 below, and kneaded for 30 minutes to obtain the compositions of the Examples and Comparative Examples.

[0108] Molding method After mixing, the compositions shown in Table 1 are obtained.

[0109] The obtained composition from Table 2 was injected into a 60mm×60mm×6mm mold and molded using a compression molding machine at 100°C for 60 minutes.

[0110] Evaluation methods Thermal conductivity: The compositions in Tables 1 and 2 were poured into a 60mm×60mm×6mm mold to test their thermal conductivity.

[0111] The compositions obtained in the examples and comparative examples in Table 2 were cured into 6 mm thick sheets at 100°C for 60 minutes. The thermal conductivity of the sheets was measured using two sheets and a thermal conductivity meter (trade name: TC3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) was used.

[0112] hardness: The compositions obtained in the examples and comparative examples in Table 2 were cured into 6 mm thick sheets in the same manner as described above, and two sheets were overlapped and the Shore 00 was measured using a Zwick hardness tester.

[0113] Density: determined using Mettler Toledo ML204.

[0114] Table 1 Silicone Grease Compositions

[0115] Table 1 shows that, with the same proportions of small, medium, and large particle sizes of aluminum hydroxide, a comparison between Ex.1 and C.Ex.1 reveals that the silicone grease composition obtained from Ex.1 (using aluminum hydroxide with an average particle size of 90 μm (C-3)) has lower viscosity and higher thermal conductivity than the silicone grease composition obtained from C.Ex.1 (using aluminum hydroxide with an average particle size of 50 μm (C-4-1)). Similarly, a comparison between Ex.3 and C.Ex.3 shows that the silicone grease composition obtained from Ex.1 (using aluminum hydroxide with an average particle size of 90 μm (C-3)) has lower viscosity and higher thermal conductivity than the silicone grease composition obtained from C.Ex.3 (using aluminum hydroxide with an average particle size of 110 μm (C-4-2)). In other words, within the traditionally considered large particle size range of 40-150 μm for aluminum hydroxide, the inventors have found that using aluminum hydroxide with an average particle size around 90 μm yields superior performance.

[0116] Furthermore, when the ratio of (C-1): (C-2): (C-3) is 2:2:6, the product obtained by Ex.1 has significantly lower viscosity and higher thermal conductivity than the product of C.Ex.4.

[0117] Table 2 Thermally conductive sealant compositions

[0118] Table 2 shows that the sealant product obtained by Ex.10 (using aluminum hydroxide with an average particle size of 90 μm (C-3)) has lower viscosity and higher thermal conductivity than the sealant product obtained by C.Ex.10 (using aluminum hydroxide with an average particle size of 50 μm (C-4-1)).

Claims

1. A composition comprising: (A) component, which is (A-1) component, which is an organopolysiloxane having at least two alkenyl groups in one molecule; Optional component (B) is an organohydrogen-containing polysiloxane having at least two hydrogen atoms directly bonded to silicon atoms, wherein the amount of hydrogen atoms directly bonded to silicon atoms is 0.1 to 5.0 times the amount of alkenyl groups derived from component (A-1). (C) Component thermally conductive filler, (C) component contains 10-25wt% (C-1) aluminum hydroxide with an average particle size greater than or equal to 0.1μm and less than 4μm. 18-37wt% (C-2) Aluminum hydroxide with an average particle size greater than or equal to 4μm and less than or equal to 20μm. 48-65wt% (C-3) aluminum hydroxide with an average particle size greater than or equal to 80μm and less than or equal to 100μm. Of (C-1), (C-2), and (C-3), based on a 100wt% content of component (C) in the composition, Optional component (D), which is a platinum group metal solidified catalyst, is 0.1-1,000 ppm relative to component (A-1) in terms of the mass of platinum group metals. The thermally conductive filler content is greater than or equal to 0.88, and The total amount of aluminum hydroxide used is greater than 95 wt%, calculated based on the total amount of thermally conductive fillers being 100 wt%.

2. The composition of claim 1, wherein the sum of all aluminum hydroxide amounts is greater than 99 wt%, calculated based on a total thermally conductive filler amount of 100 wt%.

3. The composition of claim 1 or 2, wherein the density of the composition is less than or equal to 2.4 g / cm³. 3 .

4. The composition of claim 1 or 2, wherein the density of the composition is less than or equal to 2.2 g / cm³. 3 .

5. The composition of claim 1 or 2, wherein the density of the composition is less than or equal to 2.1 g / cm³. 3 .

6. The composition of claim 1 or 2, wherein the thermal conductivity of the composition is greater than or equal to 3.1 W / mK.

7. The composition of claim 1 or 2, wherein the weight ratio of component (C) to component (E-1) is between 100 and 800. Component (E-1) is an alkoxysilane compound represented by the following general formula (1). R 1 a R 2 b Si(OR 3 ) 4-a-b (1) In the formula, R 1 Independently, it is an alkyl group having 1-24 carbon atoms, R 2 For methyl, ethyl, R 3 Independently, it is an alkyl group having 1-6 carbon atoms. a is an integer from 1 to 3, b is an integer from 0 to 2, and a+b is an integer from 1 to 3.

8. The composition of claim 1 or 2, wherein component (C) contains 10-20wt% (C-1) aluminum hydroxide with an average particle size greater than or equal to 0.5μm and less than or equal to 3μm. 20-35wt% (C-2) aluminum hydroxide with an average particle size greater than or equal to 7μm and less than or equal to 15μm. 50-60wt% (C-3) aluminum hydroxide with an average particle size greater than or equal to 85μm and less than or equal to 95μm. In (C-1), (C-2) and (C-3), the composition is calculated based on (C) component being 100 wt%.

9. The composition of claim 1 or 2, wherein the ratio of the average particle size of (C-3) / (C-2) is between 7.0 and 12.

0.

10. The composition of claim 1 or 2, wherein the weight ratio of (C-1) / (C-3) is between 0.2 and 0.

4.

11. The composition of claim 1 or 2, wherein the weight ratio of (C-2) / (C-3) is between 0.2 and 0.

8.

12. The composition of claim 7, wherein component (E-1) is 1-100 parts by mass relative to 100 parts by mass of component (A).

Citation Information

Patent Citations

  • Thermally conductive polymer and resin compositions for producing same

    CN104718254A

  • Platinum-olefin complex catalyzed addition of hydrogen- and alkenyl-substituted siloxanes

    US3159601A

  • Addition reaction

    US3159662A

  • Organosilicon process using a chloroplatinic acid reaction product as the catalyst

    US3220972A

  • Platinum complexes of unsaturated siloxanes and platinum containing organopolysiloxanes

    US3775452A